Characteristics of Children, Youth, and Young Adults With Diabetes: A Cross-Sectional Study in New Zealand Aotearoa - Sara Mustafa; Ryan Paul; Rawiri Keenan; Dianna Magliano; Lynne Chepulis (Journal of Diabetes Research)
Conclusions: The increasing burden of diabetes among young individuals in New Zealand underscores the urgent need for comprehensive strategies to address obesity and socioeconomic disparities, especially among marginalised communities. Addressing socioeconomic factors such as affordable housing, living wages, and healthcare access may be important for improving diabetes outcomes, as these factors significantly influence overall childhood health and well-being.